2015
DOI: 10.1002/ange.201504865
|View full text |Cite
|
Sign up to set email alerts
|

Weak‐Acid Sites Catalyze the Hydrolysis of Crystalline Cellulose to Glucose in Water: Importance of Post‐Synthetic Functionalization of the Carbon Surface

Abstract: The direct hydrolysis of crystalline cellulose to glucose in water without prior pretreatment enables the transformation of biomass into fuels and chemicals. To understand which features of a solid catalyst are most important for this transformation, the nanoporous carbon material MSC‐30 was post‐synthetically functionalized by oxidation. The most active catalyst depolymerized crystalline cellulose without prior pretreatment in water, providing glucose in an unprecedented 70 % yield. In comparison, virtually n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…To et al . using MSC‐30, a high surface‐area commercially available nanoporous material, also demonstrated the importance of oxidative surface functionalization of carbon catalyst. They were using HNO 3 and NaOCl solutions as oxidation agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To et al . using MSC‐30, a high surface‐area commercially available nanoporous material, also demonstrated the importance of oxidative surface functionalization of carbon catalyst. They were using HNO 3 and NaOCl solutions as oxidation agents.…”
Section: Discussionmentioning
confidence: 99%
“…To et al . suggested that local density of weak‐acid sites on the external surface of carbon catalyst can be in direct solid‐solid contact with the crystalline‐cellulose surface for catalyzing the depolymerization reaction. Hence, we tentatively propose that phenolic groups can form hydrogen bonds with hydroxyl groups in beta‐1,4‐glycosidic bonds of a cellulose chain and the adjacent carboxylic acids or hydroxyl groups have an opportunity to activate glycosidic bonds in the strands toward hydrolysis, by the same intramolecular general acid catalysis mechanism invoked by Capon .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the most abundant source of biomass and one of the most widely distributed and abundant polysaccharides in nature, cellulose provides more possibilities for sustainable chemicals and fuels in the future (Huber et al, 2006;Climent et al, 2014;Sheldon, 2014;To et al, 2015). Hence, the conversion of cellulose could become a significant part of biomass utilization, which plays an important role in the development of chemicals and fuels in the future.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to its robust crystal structure with high chemical stability, depolymerization of cellulose through solid–solid interactions with solid synthetic catalysts requires substantial pretreatments, which remarkably increases the number of processing steps and hence the energy and environmental cost . Recently, inspired by the concept that weakly acidic and water‐tolerant carbons might be potentially useful for the hydrolysis of cellulose, carbon catalysts carrying weak‐acid sites (i.e., carboxylic and phenolic groups) have been synthesized and used for the decomposition of cellulose without pretreatment in water, providing appreciable glucose yield . Nevertheless, the reaction temperature of reported aqueous systems is still very high, and the yield of glucose is not satisfactory.…”
Section: Introductionmentioning
confidence: 99%